2010
DOI: 10.1074/jbc.m109.078964
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of UvrD Helicase Activity by Covalent DNA-Protein Cross-links

Abstract: UvrD (DNA helicase II) has been implicated in DNA replication, DNA recombination, nucleotide excision repair, and methyl-directed mismatch repair. The enzymatic function of UvrD is to translocate along a DNA strand in a 3 to 5 direction and unwind duplex DNA utilizing a DNA-dependent ATPase activity. In addition, UvrD interacts with many other proteins involved in the above processes and is hypothesized to facilitate protein turnover, thus promoting further DNA processing. Although UvrD interactions with prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…It has been shown that DPCs impede the progression of the UvrD helicase involved in nucleotide excision repair only when placed on the translocating strand (14). The progression of T7 RNA polymerase that transiently disrupts dsDNA for transcription is also blocked by DPCs only when DPCs are placed on the transcribed strand (17).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DPCs impede the progression of the UvrD helicase involved in nucleotide excision repair only when placed on the translocating strand (14). The progression of T7 RNA polymerase that transiently disrupts dsDNA for transcription is also blocked by DPCs only when DPCs are placed on the transcribed strand (17).…”
Section: Discussionmentioning
confidence: 99%
“…The DinG, UvrD, and Rep helicases have been implicated in preventing or mitigating the damage from collisions between the replication machinery and bound proteins (such as RNA polymerase), and at least Rep and UvrD have protein removal activity in vitro (13,1820). Specific to blocked transcription complexes, Mfd, the transcription-coupled repair factor in bacteria, recognizes RNAP stalled at DNA damage such as a pyrimidine dimer, removes RNAP from the DNA, and recruits excision repair machinery (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to repair, DPCs impair the loading of UvrB, a damagerecognition protein involved in bacterial nucleotide excision repair (NER), onto the DPC site in a DPC size-dependent manner (7). The progression of the bacterial NER helicase (UvrD) is severely blocked when the DPC is present in the translocating strand (8). In mammalian cells the upper size limit of crosslinked proteins (CLPs) amenable to NER is around 8 kDa, eliminating the role of NER in the repair of DPCs in vivo (9).…”
mentioning
confidence: 99%